The Responsibilities of Land Deed Officials in Cases of Legally Null and Void Sale Agreements - Yusmar, Raffika; Sulityarini, Rachmi; Hadisuryo, Hendarto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Land Deed Official (PPAT) often finds themselves as the defendant in legal cases. One notable example is the decision from the Makassar District Court No. 126/Pdt.G/2019/PN Mks. The purpose of this research is to analyze the responsibilities of the Land Deed Official (PPAT) when the deed they have prepared is declared null and void by law. This study employs a normative legal research approach, utilizing both legislative and case study methods. The legal materials for this research consist of primary legal materials and secondary legal materials, which will be analyzed using systematic interpretation and grammatical interpretation techniques. The findings indicate that the PPAT, as a public official responsible for drafting the Sale and Purchase Deed in Decision No. 126/Pdt.G/2019/PN Mks, must be accountable for the deed they create from an administrative perspective. This deed was declared null and void due to the failure to meet the contractual elements; consequently, the PPAT faced only administrative sanctions based on the ruling.